2015
DOI: 10.1016/j.elecom.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical kinetics of the hydrogen reaction on platinum in concentrated HCl(aq)

Abstract: The hydrogen reaction in concentrated HCl(aq) solutions is a key reaction for the CuCl(aq)/HCl(aq) electrolytic cell. Here, electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV) were used to obtain new data for the hydrogen reaction on platinum submerged in highly concentrated acidic solutions at 25 °C and 0.1 MPa. LSV and EIS data were collected for Pt in 0.5 mol/L H 2 SO 4 (aq), 1 mol/L HCl(aq) and 7.71 mol/L HCl(aq) solutions. It was found that exchange current density (j 0 ) value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Canada Nuclear Laboratories (formerly Atomic Energy of Canada Limited) demonstrated hydrogen production by a CuCl electrolyzer continuously for several days and reported that electrolysis is feasible at low potentials (0.6‐0.7 V) at a current density of 0.1 A cm −2 using inexpensive materials . The Pennsylvania State University has carried out comprehensive experiments and theoretical developments on the cycle . Balashov et al performed an experimental study on a CuCl/HCl electrolyzer and reported a voltage efficiency of 80% and a current efficiency of 98%, which is with a good agreement with Faraday law.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Canada Nuclear Laboratories (formerly Atomic Energy of Canada Limited) demonstrated hydrogen production by a CuCl electrolyzer continuously for several days and reported that electrolysis is feasible at low potentials (0.6‐0.7 V) at a current density of 0.1 A cm −2 using inexpensive materials . The Pennsylvania State University has carried out comprehensive experiments and theoretical developments on the cycle . Balashov et al performed an experimental study on a CuCl/HCl electrolyzer and reported a voltage efficiency of 80% and a current efficiency of 98%, which is with a good agreement with Faraday law.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, z r denotes number of electrons in each half‐reaction. For the anode, assuming a one‐step reaction, exchange current density can be determined as follows: inormalo,anode=Fknormalo,anode()cox1normalαcredα where c ox and c red denote molar concentrations of the oxidant and the reductant of the half‐cell reaction at the anode. In Equation , for example, the ion CuCl3()aq is the oxidant and CuCl32()aq is the reductant of the anode half‐reaction.…”
Section: Electrochemical Modeling and Kinetic Analysismentioning
confidence: 99%
See 3 more Smart Citations